Identification of Active Compound and Effectiveness Test of 96% Tithonia diversifolia Ethanol Extract on Mortality of Aedes aegypti Mosquito - A.P, Gadila; Mustofa, Syazili; Graharti, Risti; Setyaningrum, Endah (CV. Jasa Sukses Abadi, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical regions, with Asia accounting for 70% of global cases and Indonesia reporting a massive 90,269 cases in 2024. Vector control is the primary mitigation strategy due to limitations in available therapies and vaccines, yet reliance on chemical insecticides poses ecological toxicity and resistance risks, driving the need for safer bioinsecticide alternatives. Tithonia diversifolia is known to contain active phytochemical constituents with insecticidal potential. This true experimental study used a Post Test Only with Control Group design conducted from August to September 2025 involving 25 Aedes aegypti per group with four replications. Leaf simplicia were extracted using 96% ethanol, followed by alcohol-free verification, qualitative phytochemical screening, and formulation into spray preparations at concentrations of 5%, 10%, 15%, 20%, and 25%. Mortality was assessed over 24 hours, and statistical evaluation included univariate, bivariate, and probit analyses to determine LC50, LC90, LT50, and LT90. Extraction produced a 12.53% yield containing saponins, flavonoids, phenols, tannins, alkaloids, and steroids. Mosquito mortality increased with rising concentrations, with the highest effectiveness observed at 25%. The Kruskal–Wallis test confirmed significant differences between groups, while LC50 and LC90 values were 2.77% and 5.37%, respectively. Although the highest mortality was observed at 25%, the 20% concentration was considered optimal because it met WHO efficacy standards while using a lower extract concentration.